Penanaman Nilai-Nilai Kemasyarakatan Di Pesantren Modern - Ahmad Nadjib H.; Muh. Jamaluddin; Hilman Haroen; Taufik Nugroho; Paiman Paiman (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2019)
The modern Pabelan Islamic boarding school has received awards in relation to community welfare development including the international Aga Khan Award and the Kalpataru Environment national award. The noble values ​​in the pesantren culture that are to be implanted in the Pabelan modern Islamic boarding school require further exploration so that the strengthening of character education (PPK) based on the culture of the pesantren has various alternatives according to the specifics of each, especially those related to the process of cultivating social values ​​in extra-curricular activities. The case study research in a qualitative approach concludes that the internalization of social values ​​in Panca Jiwa, the motto of the boarding school and its educational orientation has been evident in the culture of Pesantren in extracurricular activities of trilingual speech and scouting with active participation of all parties in the pesantren and clear rules and regulations. hence strengthening the interaction between the community and the pesantren is needed by actively involving the community in extracurricular activities as a whole. Collective and individual initial guidance for new santri on societal values ​​also has a positive impact on the internalization of the pesantren culture for each Pabelan Pesantren student on an ongoing basis.